Apolar Compounds in Seaweeds from Fernando de Noronha Archipelago (Northeastern Coast of Brazil) - Leandro De Santis Ferreira; Izabel Cristina Casanova Turatti; Norberto Peporine Lopes; Thais Guaratini; Pio Colepicolo; Eurico Cabral Oliveira Filho; Ricardo Clapis Garla (International Journal of Analytical Chemistry)
Hyphenated techniques of gas chromatography coupled to mass spectrometer were used to determine fatty acids in eleven species of seaweeds from Fernando de Noronha archipelago. The main compounds detected in all studied species were the alcohol phytol and the fatty acids 14 : 0; 15 : 0; 16 : 0; 18 : 0; 18 : 1 n9; 18 : 2 Δ9,12; 20 : 4; 20 : 5. These fatty acids are commonly found in seaweeds present in warm regions. Thus, we found no specificity in the presence of a particular set of fatty acids and the studied species indicating that they are not useful as taxonomic indicators. However, they could be used in a comparative study with algae found in polluted area because many of the studied seaweeds are widespread and Fernando de Noronha has low human influence.